Evaluation of the cytotoxicity activity inthe leaves of Nilgirianthus Ciliatus (LINN) in Dalton’s Lymphoma ascites cells - NEETHU VARGHESE; JEMI JACOB (International Journal of Pharma and Bio Sciences, 2018)
Cancer is a disease in which there is uncontrolled multiplication and spread within the body of abnormal forms of the body’s own cell. Some preclinical studies suggest that phytochemicals can prevent some types of cancers. More than 60% of currently used anticancer agents are derived in one way or another from natural sources. Cell line studies can serve as an initial screen for the phytoconstituents in controlling the cell multiplication. The current study aims to assess the cytotoxic activity of select extracts of the leaves of Nilgirianthus ciliatus Linn. In this study, different concentrations of the extracts were subject to cytotoxic activity against DLA (Dalton’s Lymphoma Ascites) bearing mice by using the trypan blue exclusion method. Cell viability was inhibited to different extent by using different concentrations of the extracts. The tested extracts showed significant IC50 values for the tested cell line. This indicates the selective cytotoxicity towards the cancer cells. Among the extracts screened, the Petroleum ether extract of Nilgirianthus ciliatus Linn was identified to possess potential cytotoxic activity with an IC50 value of 116.57 μg/ml. The plant showed significant anti-cancer potential and can be used to discover bio-active natural products that may serve as leads for the development of new anti-neoplastic agent.